Types of recurrence of the administrative offences - Chakarova-Dimitrova, Izabela (Law Journal of New Bulgarian University, 2024)
The present article dwells on the different types of recurrence of the administrative offences. The author attempts to define the different types of recurrence of the administrative offences and to analyze their most important characteristics. The author examines the prerequisites of the recurrence of the administrative offences under the special legislation.